Early serum biomarker networks in infants with distinct retinochoroidal lesion status of congenital toxoplasmosis. (July 2017) - de Araújo, Thádia Evelyn; Coelho-dos-Reis, Jordana Grazziela; Béla, Samantha Ribeiro; Carneiro, Ana Carolina Aguiar Vasconcelos; Machado, Anderson Silva; Cardoso, Ludmila Melo; Ribeiro, Ágata Lopes; Dias, Michelle Hallais França; Queiroz Andrade, Gláucia Manzan; Vasconcelos-Santos, Daniel Vitor; Januário, José Nélio; Teixeira-Carvalho, Andréa; et al.
Abstract: The present study characterized the early changes in the serum chemokines/cytokine signatures and networks in infants with congenital-toxoplasmosis/(TOXO) as compared to non-infected-controls/(NI). TOXO were subgrouped according to the retinochoroidal lesion status as no-lesion/(NL), active-lesion/(ARL), active/cicatricial-lesion/(ACRL) and cicatricial-lesion/(CRL). The results showed that TOXO display prominent chemokine production mediated by IL-8/CXCL8, MIG/CXCL9, IP-10/CXCL10 and RANTES/CCL5. Additionally, TOXO is accompanied by mixed proinflammatory/regulatory cytokine pattern mediated by IL-6, IFN-γ, IL-4, IL-5 and IL-10. While TNF appears as a putative biomarker for NL and IFN-γ/IL-5 as immunological features for ARL, IL-10 emerges as a relevant mediator in ACRL/CRL. IL-8/CXCL8 and IP-10/CXCL10 are broad-spectrum indicators of ocular disease, whereas TNF is a NL biomarker, IFN-γ and MIG/CXCL9 point out to ARL; and IL-10 is highlighted as a genuine serum biomarker of ACRL/CRL. The network analysis demonstrated a broad chemokine/cytokine crosstalk with divergences in the molecular signatures in patients with different ocular lesions during congenital toxoplasmosis.